2004
DOI: 10.1177/0363546504263702
|View full text |Cite
|
Sign up to set email alerts
|

Healing Potential of Meniscal Tears without Repair in Knees with Anterior Cruciate Ligament Reconstruction

Abstract: Stable meniscal tears at the time of anterior cruciate ligament reconstruction possibly could be left in situ. However, longer medial meniscal tears are thought to require additional stabilizing procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
60
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 35 publications
6
60
0
1
Order By: Relevance
“…6,[20][21][22][23][24][25] However, the reported 16% reoperation rates in this study are comparable to rates reported in other studies [24][25][26] when we are able to hone in on more specific criteria and the morphologic characteristics of the tears. Furthermore, isolated trephination does offer some specific advantages to suture or device repair of the meniscus.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…6,[20][21][22][23][24][25] However, the reported 16% reoperation rates in this study are comparable to rates reported in other studies [24][25][26] when we are able to hone in on more specific criteria and the morphologic characteristics of the tears. Furthermore, isolated trephination does offer some specific advantages to suture or device repair of the meniscus.…”
Section: Discussionsupporting
confidence: 85%
“…No distinction was made between tear lengths or whether the meniscus tear was full thickness or partial thickness. However, we believe that the simplicity of our repair criteria and application to all tears of this type regardless of those specific criteria are in line with the findings of Yagishita et al, 25 who found no relationship between tear length and meniscus tear healing. Finally, no analysis related to associated articular cartilage damage was performed for this study, which might affect the results.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…9 Three studies looked at meniscal healing after being left in situ (2 with second-look arthroscopy, 1 with either second-look arthroscopy or arthography), finding complete healing in 50% to 61% of medial meniscal tears and 55% to 74% of lateral tears. 4,36,37 An observer asking what all this means for the treatment of patients must first define whether surgical success or patient quality of life is the (2) will I be at greater risk of arthritis in the future? The previous studies suggest that repair of certain types of tears may do more to make the surgeon feel better about the situation than truly be of benefit to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Pierre et al (22) estudaram as lesões do menisco não tratadas em pacientes submetidos à reconstrução do LCA e concluíram que as lesões do menisco medial superiores a 10mm devem ser tratadas. Yagishita et al (23) observaram que, não obstante o potencial de cicatrização dessas lesões do menisco encontradas durante a reconstrução do LCA, as lesões mais longas devem ser reparadas. Em nosso estudo, todas as lesões viáveis acima de 20mm foram reparadas e as menores, excluídas da análise.…”
Section: Discussionunclassified